A nonfullerene acceptor for wide band gap polymer based organic solar cells. Issue 3 (9th November 2015) - Zhang, Jicheng; Zhang, Xuejuan; Li, Guangwu; Xiao, Hongmei; Li, Wenhua; Xie, Sufei; Li, Cuihong; Bo, Zhishan
Abstract : A small molecular acceptor was synthesized for wide band gap polymer based nonfullerene OPVs to achieve a PCE of 3.71%, which is the best value for nonfullerene OPVs with a V oc higher than 1 V. Abstract : A new 1, 8-naphthalimide based planar small molecular acceptor and two benzothiadiazole based wide band gap (WBG) polymer donorsP1 andP2 were synthesized for nonfullerene organic photovoltaic cells (OPVs). Devices based on fluorinated polymerP2 achieved a highly improved PCE of 3.71% with an open circuit voltage ( V oc ) of 1.07 V, which is beyond the currently known levels for nonfullerene OPVs with the V oc higher than 1 V.